Curing of ground ham by remote infusion of atmospheric non-thermal plasma. (30th March 2020) - Jo, Kyung; Lee, Juri; Lee, Seonmin; Lim, Youbong; Choi, Yun-Sang; Jo, Cheorun; Jung, Samooel
Highlights: Remote infusion of ANP generated nitrite in meat batter with a weak heating effect. Ground ham cured by the remote infusion of ANP had a low pH. Residual nitrite in ground ham cured by ANP rapidly decreased during storage. Ground ham cured by ANP had good color and lipid oxidation properties. Abstract: This study investigated the changes in the nitrite content and temperature of meat batter with the remote infusion of atmospheric non-thermal plasma (ANP) and the quality properties of ground hams cured by remote infusion of ANP. Remote infusion of ANP for 14.78 min generated 100 mg kg −1 of nitrite in 3.2 kg meat batter, and the meat batter temperature increased from 1.8 to 9.2 °C. The residual nitrite content of ground ham cured by the remote infusion of ANP (RANP) was higher than that of ground ham cured with sodium nitrite (SN) at 1 day of storage (p < 0.05); however, no difference between RANP and SN was observed after 30 days of storage (p > 0.05). The color and malondialdehyde content of ground hams did not differ between RANP and SN during storage (p > 0.05). The remote infusion ANP system could be applied to cure meat products without the addition of nitrite sources.